Determine the integral of y=(x+3)/(x^2-9)?

### 1 Answer | Add Yours

You need to evaluate the given indefinite integral, hence, you should first reduce the integrand to the most simplified form, such that:

`(x + 3)/(x^2 - 9) = (x + 3)/((x - 3)(x + 3))`

Reducing the duplicate factors, yields:

`(x + 3)/(x^2 - 9) = 1/(x - 3)`

Hence, evaluating the indefinite integral, yields:

`int (x + 3)/(x^2 - 9) dx = int 1/(x - 3) dx`

You should come up with the following substitution, such that:

`x - 3 = t => dx = dt`

Replacing the variable, yields:

`int 1/(x - 3) dx = int 1/t dt`

`int 1/t dt = ln|t| + c`

Replacing back `x - 3` for t yields:

`int 1/(x - 3) dx = ln|x - 3| + c`

**Hence, evaluating the given indefinite integral, yields ****`int (x + 3)/(x^2 - 9) dx = ln|x - 3| + c` .**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes